Advances and applications in fetal magnetic resonance imaging. (July 2015) - Story, Lisa; Rutherford, Mary
<x xml:space="preserve">Abstract</x> Key content This article describes recent advances in the use of magnetic resonance imaging (MRI) in the fetus to overcome some of the difficulties associated with unpredictable fetal motion. Improvements in acquisition and post‐acquisition software that enable brain structures to be evaluated in greater detail, allowing the assessment of both normal and abnormal development, are discussed. This article discusses the current clinical applications and imaging techniques and their complementary role to ultrasound. Learning objectives To be able to assess safety of using MRI in the fetus and pregnant woman. To learn about the current applications of MRI and when referral may be beneficial. To be aware of potential future developments of MRI. Ethical issues The safety of the mother and fetus must be considered.